Monitoring livestock development schemes. Botswana, socio-economic monitoring of the Tribal Grazing Land Programme - Haaland, G. (International Livestock Centre for Africa, 1978)
Describes two approaches namely, anthropological in-depth studies of a few communities and social surveys, that can be used in socio-economic monitoring of the Tribal Grazing Lands Programme (TGLP), Botswana; w. an annex on the need to define & demarcate social units and implications of national & international economic context, adaptability of dif. social units, participation of the people, grazing rights, and relations between livestock & agriculture in communal areas in the implementation of TGLP.